If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x * 0 + -9y = 63 Reorder the terms for easier multiplication: -7 * 0x + -9y = 63 Multiply -7 * 0 0x + -9y = 63 Anything times zero is zero. 0x + -9y = 63 Remove the zero: -9y = 63 Solving -9y = 63 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-9'. y = -7 Simplifying y = -7
| 2x^2-3-x=0 | | 5x+38=2x+62 | | k/4=3/8 | | -7x-9*0=63 | | =(3x+1)(2x+1) | | -3(1+4x)=-4x-5 | | 7x+49=2x+49 | | -5x=9-y | | 2L^2-6L-20=0 | | 3x-4-16=2x-16+7 | | u^2=144 | | 5m+7=4m+12 | | 120=1/2[(360-X)-x] | | -3x-7*0=21 | | Y+1=7(x+3) | | x=4ln(10)-4ln(5) | | -5e^2x=25 | | x=4ln(5) | | 7.56x+25=57.1536+5x | | 2x-(-x-3)=-2x-3 | | 8a+2=6a-8 | | kx^2-26x+51=0 | | 54=-6(3x+18) | | 5x-5=4x-13 | | 20=2x-3(4x+10) | | (x)3/32=54 | | [(x+10)-24]+(x+10)+x=180 | | -2-2x-5=-x-3(x-1) | | y-23=9 | | -5.8(3t+5)-2.5(2t-6)= | | 5x-2(-2y+4x)-5y= | | log(3x-2)5=3 |